2018
DOI: 10.1111/his.13695
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of tumour‐infiltrating lymphocytes in breast cancer and its prognostic significance

Abstract: Despite the heterogeneity of immune cell type components, average TILs in one full-face H&E-stained section reliably represent TILs in the whole tumour. TILs were associated with outcome in TNBC patients, as well as having prognostic significance for recurrent tumours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 40 publications
(84 reference statements)
4
48
0
Order By: Relevance
“…Most previous studies focused on the prognostic effect of individual cell subsets [24][25][26]. Ali et al confirmed a positive correlation between B cells and prognosis and clustered breast cancer patients into 8 types according to immune cell subsets distribution [25].…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies focused on the prognostic effect of individual cell subsets [24][25][26]. Ali et al confirmed a positive correlation between B cells and prognosis and clustered breast cancer patients into 8 types according to immune cell subsets distribution [25].…”
Section: Discussionmentioning
confidence: 99%
“…Manipulation of this interaction is a fast-growing field, and several immune checkpoint inhibitors have been described in several solid cancers including BC which show highly promising results for therapy [52, 53]. There is sufficient evidence to demonstrate that moderate and intense inflammation is associated with improved prognosis in triple-negative (TN) and HER2-positive BC [54-56]. TILs comprise several types of immune cells, including tumour-promoting and tumour-suppressing cells.…”
Section: Interaction With the Surrounding Microenvironmentmentioning
confidence: 99%
“…Survival data were available and prospectively maintained, including (i) BC-specific survival (BCSS), defined as the duration (in months) from the date of the primary surgical treatment to the time of death from BC, and (ii) distant metastasis-free survival (DMFS), defined as the duration (in months) from surgery to the first event of distant metastasis. 15,16 The mean follow-up period of the study cohort was 130 months, median was 120 months and the range was 239 months. Patients were uniformly treated based on tumour features, NPI and hormone receptor status.…”
Section: T U M O U R C H a R A C T E R I S T I C S O F T H E S T U D mentioning
confidence: 99%